2023
DOI: 10.1039/d3qi00555k
|View full text |Cite
|
Sign up to set email alerts
|

Metal-involved C⋯dz2-PtIItetrel bonding as a principal component of the stacking interaction between arenes and the platinum(ii) square-plane

Abstract: The half-lantern PtII2 complexes [Pt(CN)(μ-SN)]2 (HCN = 2-phenylbenzothiazolate 1; 2-naphtylbenzothiazolate 2; HSN = 2-thiopyridine) were crystallized with such electron-deficient arenes as hexafluorobenzene (C6F6) and octafluoroanthraquinone (OFA) to give cocrystals 1·C6F6,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 71 publications
1
14
0
Order By: Relevance
“…The ρ b and ∇ 2 ρ b values of the C⋯Pt contact decrease along the row of halogens from F to I which may suggest a weakening of this interaction from [ 1 ·QF] to [ 1 ·QI]. The C⋯Pt interaction exhibits a high value of bond ellipticity in all structures ( ε = 1.4–8.8); this effect has been previously observed 56 for the C⋯Pt contacts in the cocrystals of [Pt( pbt )(μ-S ∩ N)] 2 (S ∩ N = 2-thiopyridine, pbt = 2-phenylbenzothiazole) with electron-deficient arenes.…”
Section: Resultssupporting
confidence: 64%
See 3 more Smart Citations
“…The ρ b and ∇ 2 ρ b values of the C⋯Pt contact decrease along the row of halogens from F to I which may suggest a weakening of this interaction from [ 1 ·QF] to [ 1 ·QI]. The C⋯Pt interaction exhibits a high value of bond ellipticity in all structures ( ε = 1.4–8.8); this effect has been previously observed 56 for the C⋯Pt contacts in the cocrystals of [Pt( pbt )(μ-S ∩ N)] 2 (S ∩ N = 2-thiopyridine, pbt = 2-phenylbenzothiazole) with electron-deficient arenes.…”
Section: Resultssupporting
confidence: 64%
“…We previously reported that CT plays a crucial role in the noncovalent tetrel π-hole C⋯Pt interactions in the complexes [Pt( pbt )(μ-N ∩ S)] 2 ·Ar F (N ∩ S = 2-μ-mercaptopyridine, Ar F = perfluoroarene). 32 The total NBO/AIM atomic charges of QF in [ 1 ·QF] are −45/–88 me, which corresponds to the total CT from 1 to QX upon the generation of [ 1 ·QX]. In the cases of [ 1 ·QCl] and [ 1 ·QBr], these atomic charges are close to −14/–30 me, while for QI there are no more than −10/–8 me.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2-phenylbenzothiazoles have also shown interesting metal-involved noncovalent interactions [ 27 , 28 , 29 , 30 ] with broad applications in materials science, while in the diagnostic area, many metal-radiolabeled 2-phenylbenzothiazole derivatives are continuing to be explored as amyloid imaging agents [ 23 , 31 , 32 , 33 ]. Non-metal-based positron emission tomography (PET) imaging of Aβ plaques is also possible through the use of radiolabeled benzothiazoles such as the 18 F-labeled derivative of 2-(4-aminophenyl)benzothiazole [ 18 F] Flutemetamol, which gained approval in 2013 for clinical use [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%